Models of Language Teaching and Humanizing Education - Rosida Tiurma Manurung (CAKRAWALA LINGUISTA, 2018)
Modern, digitalized, high tech, global era characterized by the development of sciences has transform human beings into heartless machines with no sense of humanity and no concerns to their surrounding environment. Therefore, education should be packed with loads that include the perspective of humanism. Education should not be interpreted as a mere class teaching-learning activity. Education should refer to the various processes and activities that should be productive; creative; develop skills, personality, integration, and excellence; and up to moral and spiritual reinforcement.  Education shall be managed and directed with clear objectives, which are capable to develop positive values in learners. Education should be able to create figures with solid and proven character and personality both in the field of science and the humanities. Humanizing education means it is capable to produce human with sense of "humanity" which is characterized by the willingness to help others; empathy; honesty; share; loyalty; the willingness to take valuable lessons; persistent and tenacious,; high-respect of pluralism; tolerance; respect to others; patience; replied good for evil; always puts the good rather than evil, continuous efforts to improve the quality of charity and kindness; humility; and sincere. Therefore, the teaching materials must also be interpreted, filled, and imbued with the messages of humanity. These entire facts mean that teaching materials are not mere “soulless and empty” materials since if it is, then the materials will be like empty casket with no benefit to human life and livelihood. Approach of humanism in modern era education is considered as the most appropriate solution since this kind of education has education activities that don’t works like the machines do, and this means the students, teachers, and teaching materials should also be “humanized” in order to achieve educational goals optimally and in accordance with the vision and mission carried. This research discuss model of language teaching with humanistic perspective. Hopefully, through language teaching with humanism approach, students and teachers may rediscover the "human side" that may have been lost and undetected.